A exceção e o direito: contributos para a preservação do exercício constitucional da função administrativa - Martins, Rafael Medeiros (2025)
The present dissertation investigated the characteristics and relations of contemporary authoritarianism in the Public Administration in order to create administrative categories capable of resisting authoritarian intentions. The theory of states of exception was adopted to explain the contemporary authoritarian phenomenon, drawing from it the authoritarian branch that intimately afflicts the administrative function: the neoliberal epistemology. The following administrative categories were indicated as bars of resistance against these authoritarian onslaughts: the legal-administrative regime; the bureaucratic model; the administrative act and a more refined understanding of discretionary power and, finally, the statutory regime for public servants and its consequences. The conclusion is that by recognizing how contemporary authoritarianism operates and by giving the administrative elements studied the proper composure, it is possible to avoid or at least minimize harmful political interference in public administration and thus repel neoliberal ideals that are not in line with constitutional principles and objectives